Measurement of solidification heat from supercooled water freezing during PEFC cold start and visualization of ice distribution. (8th June 2020) - Otsuki, Yota; Tamada, Yusuke; Inoue, Shoki; Shigemasa, Kaito; Araki, Takuto
Abstract: The water in polymer electrolyte fuel cells (PEFCs) operated below the freezing point interferes with the gas supply, shutting down the operation. Therefore, understanding the freezing mechanism is pivotal to achieving high-performance cold-start. In this paper, a novel method of classifying two different freezing modes using 6 μm thickness thin-film thermocouples (TFTCs) was proposed. We conducted in situ measurement of the solidification heat from supercooled water using originally developed TFTCs and further visualized the ice distribution using X-ray CT. In a mode when TFTCs measure rapid temperature rises in the −10 °C −5 °C, water freezes after diffusing into the GDL, while freezing occurs immediately inside the CL without reaching the GDL in the other mode when TFTCs measure no rapid temperature rise in the −30 °C −10 °C. These modes should be considered for future researches on components improvement, and optimization of current density sweeping to succeed the cold start. Highlights: Two different freezing modes during PEFC cold start are classified. Novel and simple method of classifying two modes using sensors was proposed. Solidification heat measured by originally developed 6 μm thickness thermocouples. Difference of ice distribution inside GDL has been visualized by X-ray CT device.